2011
DOI: 10.1016/j.pscychresns.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence for white matter metabolite differences in marijuana-dependent young men using 2D J-resolved magnetic resonance spectroscopic imaging at 4 Tesla

Abstract: Chronic marijuana (MRJ) use is associated with altered cognition and mood state, altered brain metabolites, functional and structural brain changes. The objective of this study was to apply proton magnetic resonance spectroscopic imaging (MRSI) to compare proton metabolite levels in 15 young men with MRJ-dependence and 11 healthy non-using (NU) young men. Spectra were acquired at 4.0 Tesla using 2D J-resolved MRSI to resolve coupled resonances in J-space and to quantify the entire J-coupled spectral surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 103 publications
10
52
0
Order By: Relevance
“…Five MRS studies met our inclusion criteria (Table 2) [167-171]. Four studies reported lower myo- inositol and myo- inositol/creatine ratio levels (10–36%) among regular cannabis users relative to controls [168-171].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five MRS studies met our inclusion criteria (Table 2) [167-171]. Four studies reported lower myo- inositol and myo- inositol/creatine ratio levels (10–36%) among regular cannabis users relative to controls [168-171].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported lower myo- inositol and myo- inositol/creatine ratio levels (10–36%) among regular cannabis users relative to controls [168-171]. In each study, subjects were not required to remain cannabis-abstinent prior to imaging [168-171].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies utilizing magnetic resonance spectroscopy showed alterations in glutamate, Nacetyl aspartate, creatinine and myo-nositol in the anterior cingulate [53]. Also, myo-inositol/creatine ratios were demonstrated in subcortical area as well as a reduction of myo-inositol in the white matter [52].…”
Section: Perfusion/neurotransmittersmentioning
confidence: 97%
“…Through the cannabinoid receptors, Marijuana causes changes in inhibitory as well as exitatory neuro-transmitter release. In particular alterations in dopamine, glutamate and GABA release have been shown [52]. Studies utilizing magnetic resonance spectroscopy showed alterations in glutamate, Nacetyl aspartate, creatinine and myo-nositol in the anterior cingulate [53].…”
Section: Perfusion/neurotransmittersmentioning
confidence: 99%